2021
DOI: 10.1590/1414-431x202010474
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-629-5p promotes osteosarcoma proliferation and migration by targeting caveolin 1

Abstract: Osteosarcoma is a highly malignant tumor that occurs in the bone. Previous studies have shown that multiple microRNAs (miRNAs) regulate the development of osteosarcoma. This study aimed to explore the role of miR-629-5p and its target gene, caveolin 1 (CAV1), in osteosarcoma development. To analyze the expression of miR-629-5p and CAV1 mRNA in osteosarcoma tissues and cell lines, qRT-PCR analysis was performed. Dual-luciferase reporter experiments were subsequently performed to validate the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In this study, we explored the effect of MIR22HG in osteosarcoma. In addition, it has been reported that miR-629-5p promoted osteosarcoma proliferation and migration by targeting caveolin 1 [ 9 ]. To confirm the potential interaction between MIR22HG and miR-629-5p, we first downloaded the data concerning the putative binding sites between MIR22HG and miR-629-5p from Starbase ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we explored the effect of MIR22HG in osteosarcoma. In addition, it has been reported that miR-629-5p promoted osteosarcoma proliferation and migration by targeting caveolin 1 [ 9 ]. To confirm the potential interaction between MIR22HG and miR-629-5p, we first downloaded the data concerning the putative binding sites between MIR22HG and miR-629-5p from Starbase ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Baiocchini et al, (2019) described different patterns of CAV-1 expression on LSEC and hepatocytes in the liver of HCV-infected persons vs. healthy controls, as well as a significant association between the nuclear expression of CAV-1 in hepatocytes and the stage of fibrosis [20]. Interestingly, Gao et al, (2021) showed that miR-629-5p promotes osteosarcoma proliferation and migration via the direct inhibition of CAV-1 mRNA expression [21]. In our study, we noticed that the expression of CAV-1 was downregulated when we compared F1/F2 stages of fibrosis with healthy controls and in F3/F4 stages of fibrosis compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…By combining clinical samples with public databases, we found that miR-629-5p increased to varying degrees in primary localized PCa tissues (PPCa) and metastatic PCa tissues (MPCa) compared with adjacent normal tissues (ANT), and bioinformatics analysis suggested that high level of miR-629-5p was related to poor prognosis. Although miR-629-5p has proved to play a role in promoting tumor growth and metastasis in different types of tumors such as colorectal cancer, hepatocellular carcinoma, lung adenocarcinoma and osteosarcoma (11)(12)(13)(14). However, the exact mechanism of its role in PCa metastasis remains unknown.…”
Section: Introductionmentioning
confidence: 99%